1966
DOI: 10.1111/j.1749-6632.1966.tb45504.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Specificity of Presumed Immune Associations of Myasthenia Gravis and Consideration of Possible Pathogenic Implications

Abstract: The hypothesis advanced independently in 1960 by Nastuk et. al. ' and Simpson' that myasthenia gravis is a disorder with a possible autoimmune etiology, together with studies dealing with presumed immune associations of myasthenia gravis:'-12 have recently been reviewed in detai1,l3-I5 and need not be considered here.A t the New York Academy of Sciences Conference on Autoimmunity, held in February, 1964, Strauss et al.," reported findings which essentially confirmed and extended to a larger series the various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1966
1966
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The first autoantibodies recognized with thymoma were specific for sarcomeric ("striational") proteins of skeletal muscle (14). Striational antibody specificities identified to date include titin, myosin, actin, ␣-actinin, and ryanodine receptors (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first autoantibodies recognized with thymoma were specific for sarcomeric ("striational") proteins of skeletal muscle (14). Striational antibody specificities identified to date include titin, myosin, actin, ␣-actinin, and ryanodine receptors (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Striational antibody specificities identified to date include titin, myosin, actin, ␣-actinin, and ryanodine receptors (15)(16)(17)(18). Striational antibodies and muscle AChR antibody have both been reported in patients with thymoma without evident MG (14,19). Striational antibody (20) and a high level of muscle AChR-modulating antibody activity (21) are commonly associated with thymomatous MG.…”
Section: Introductionmentioning
confidence: 99%
“…28], Thus, several nonthymoma MG sera also react strongly in the IF test. Furthermore, the staining patterns observed with sera from thymoma and nonthymoma cases are indis tinguishable [25], It could be argued that a small thymoma might be present in such cases, but escape detection. Beutner et al [5] have, however, clearly confirmed in an au topsy case that such antibodies may be present in high titers without the presence of a thymoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, 80%-90% of patients with both MG and thymoma are seropositive for StrAb [4,5,121. While the pathogenic significance of StrAb is not known, the thymus is believed to play a critical role in their induction; these antibodies bind to epithelial and myoid cells of the thymus in addition to skeletal muscle [S-71.…”
Section: Introductionmentioning
confidence: 99%